Refining the diagnostic approach to latent tuberculosis Infection with Quantiferon gold plus: A retrospective analysis of borderline results - Alba Ruedas-López; Juan María Herrero-Martínez; Alhena Reyes; Beatriz González-Blanco; Paula López-Roa (PLoS ONE, 2025)
The Quantiferon Gold Plus (QFT) test, a widely used interferon-γ release assay (IGRA), diagnoses latent tuberculosis infection (LTBI) with a positivity threshold of ≥0.35 IU/mL. Results near this cut-off can be challenging to interpret due to variability from immunological, pre-analytical, and technical factors, prompting recommendations for a borderline range to refine diagnosis and reduce overtreatment. This retrospective study analyzed QFT results from 9,944 patients (2019–2023), establishing ranges: < 0.2 IU/mL as negative, 0.2–0.35 IU/mL as borderline negative, 0.35–0.7 IU/mL as borderline positive, and >0.7 IU/mL as positive. Borderline results occurred in 7.6% of patients, particularly in those born in Africa or South America, and in older individuals. Of 64 patients retested, 60.9% reverted to negative, while 17.1% of borderline negatives later converted to positive or borderline positive. Notably, no active TB cases emerged among those who reverted to negative on repeat testing. These findings emphasize the need for cautious interpretation of borderline QFT results, as their link to active TB progression differs from clear results. The study supports repeat testing of borderline cases to enhance LTBI diagnostic accuracy and inform treatment decisions.